Arthur Rolleston (1899)
1899 "Arthur Rolleston" [t0534.jpg], 1899 Arthur Rolleston (c.1899) was the son of Robert Noonan's (Tressell's) sister, Adelaide. In 1899, Adelaide and Arthur moved to South Africa from Chile, where they had been living, to live with Robert and his daughter Kathleen. In 1901, they all returned to England, eventually making a home together in Hastings. Arthur was the inspiration for the character of Frankie, the young son of Frank Owen in 'The Ragged Trousered Philanthropists'.